Efeitos da pandemia de COVID-19 na saúde de idosos e construção do aplicativo “IDOSOFIT” para reabilitação e funcionalidade - Souza, Elenilton Correia de (2024)
Human aging is a natural, multifactorial, and continuous phenomenon. In recent years, an additional factor has worried the scientific community: the coronavirus that causes severe acute respiratory syndrome (SARS-CoV-2) has spread rapidly in Brazil and worldwide. Health indicators have shown that the group most vulnerable to severe infection and functional impairments due to COVID-19 were the elderly. The creation and registration of low-cost applications for the assessment and rehabilitation of the elderly seems to be a feasible and pioneering alternative in view of technological modernization and the acceptance of teleconsultation services. The objectives were: a) to describe the impacts of social isolation on the functionality of the elderly during the COVID-19 pandemic from a conceptual perspective of the International Classification of Functioning (ICF); b) to identify the clinical-epidemiological profile and functionality of the elderly; and c) to develop and register an application for physiotherapists and the elderly based on assessment, exercise prescription, and rehabilitation. The study was developed in three stages (M): M1: integrative review on the impacts of COVID-19 on the functionality of the elderly; M2: cross-sectional study to collect the epidemiological profile; and M3: development and registration of an application. To conduct the review in M1, the search strategy based on the following descriptors was used: “aged”, “aging”, “coronavirus infections”, “social isolation”, “disability evaluation”, “ICF” and "International Classification of Functioning, Disability and Health" combined with the Boolean operators AND or OR. Elderly people of both sexes participated in M2, randomly selected in two municipalities in Sergipe: Lagarto and Itabaiana. The following were included: a) elderly people ≥ 60 years old; b) absence of systemic instabilities that contraindicated the performance of the tests; c) having access to a cell phone and/or computer with internet; and d) not participating in other studies. Validated questionnaires on the epidemiology, clinical and functional health of the elderly were applied. All participants submitted to the informed consent form and the study was approved by the ethics committee CAAE: 52198521.0.0000.5546. In M3, the product, in partnership with the computer science department of UFS, followed the “Scrum” method, in addition to the prototyping model composed of the following steps: (I) communication, (II) rapid design, (III) modeling (rapid design), and (IV) prototype construction. The results are expressed in the three moments: M1: A total of 5,055 studies in the established databases and 2 more records identified in other sources, 5,015 were excluded after analysis of titles and abstracts and 42 were read in full. After careful reading and evaluation of the manuscripts, 7 were included in the final analysis. The evidence showed that isolation caused physical and psychological changes. M2: Sixty-eight elderly individuals were evaluated, age (70.3±6.8), weight (67.1±11.8), height (1.59±0.07). A considerable percentage of clinical and psychological changes, lifestyle changes, and factors associated with COVID-19 with impacts on the functionality of the elderly were noticeable. M3: An application was developed in 2 versions: IdosoFit web and IdosoFit Mobile, approved and registered with the National Institute of Industrial Property (INPI). The application resulted in an interface for physiotherapists who will control the recording of user information, as well as register and use exercises throughout rehabilitation sessions, in addition to an interface to encourage the independence of the patients themselves, containing information on the activity schedule and exercise progressions. Therefore, the first two studies served as an initial basis for the development of a low-cost technology for the rehabilitation of the elderly. In recent years, the need to implement health services for this population has become evident. The application, above all, allows innovations in health services and stimulates the physical capacities and autonomy of the elderly. The App facilitates the collection of clinical and epidemiological profiles of elderly people, the structuring of rehabilitation sessions, and is an important tool for the development of health in old age.